Sponge material modifier and preparation method thereof

By using tackily modified fluorosilicone resin and hydrophobically modified nanoalumina in sponge materials, the water, oil and mechanical properties of the sponge are improved, and the lack of performance of traditional sponge materials is solved, achieving performance improvement and process simplification.

CN119119569APending Publication Date: 2024-12-13WEIJIANYE (SUZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411269728.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Traditional sponge materials have shortcomings in water resistance, oil resistance and mechanical strength, which limits their application scope. The existing modification methods are complex in technology and expensive, and their performance improvement is not obvious.

Method used

Using a sponge material modifier, including tackifying modified fluorosilicone resin and hydrophobic modified nano-alumina, the water, oil and mechanical properties of the sponge are improved by introducing viscous groups and building a rough micro-nano structure. The preparation method is It was dispersed into the solvent and stirred to homogenize.

Benefits of technology

It significantly improves the water, oil and mechanical properties of the sponge, enhances its stability, tensile and compression properties, simplifies the process and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005038346160000081
    Figure BDA0005038346160000081
Patent Text Reader

Abstract

The invention relates to a sponge material modifier and a preparation method thereof, and relates to the technical field of modified materials, the sponge material modifier comprises the following components by mass: 60-80 parts of tackifying modified fluorosilicone resin, 10-20 parts of hydrophobic modified nano alumina, 3-5 parts of a leveling agent, and 80-100 parts of a solvent. The preparation method comprises the following steps: dispersing tackifying modified fluorosilicone resin, hydrophobic modified nano aluminum oxide and a flatting agent into a solvent, stirring and homogenizing to obtain the sponge material modifier. The modifier prepared by the invention can effectively improve the hydrophobic and oleophobic properties of the sponge, reduce the influence of a solvent on the sponge, and improve the stability, tensile property and compression resistance of the sponge.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of modified materials, and in particular to a sponge material modifier and a preparation method thereof. Background Art

[0002] As a porous material, sponge material is widely used in the fields of sound insulation, shock absorption, filtration, energy storage, etc. However, traditional sponge materials have some limitations in performance, such as water resistance, oil resistance, solvent resistance, mechanical strength, etc., which limit its application scope.

[0003] At present, research on the modification of sponge materials is deepening, aiming to improve their performance through chemical or physical methods. The methods commonly used to modify sponge materials include adding functional fillers, surface coating modification, chemical cross-linking, etc. Although these methods can improve the specific properties of the material to a certain extent, they often have problems such as complex processes, high costs, or insignificant performance improvements, so there is room for improvement. Summary of the invention

[0004] In order to improve the water and oil resistance of sponge, the present application provides a sponge material modifier and a preparation method thereof.

[0005] The present application provides a sponge material modifier and a preparation method thereof using the following technical solutions: In the first aspect, the present application provides a sponge material modifier, which adopts the following technical solution: A sponge material modifier comprises the following components in parts by weight: 60-80 parts of tackified modified fluorosilicone resin 10-20 parts of hydrophobically modified nano-alumina 3-5 parts of leveling agent 80-100 parts of solvent.

[0006] The viscosity-enhanced modified fluorosilicone resin improves the reactivity and adhesion of the modifier by introducing sticky groups, so that the modifier can react with the sponge and thus firmly bond. The fluorosilicone resin has good stability, low surface energy, and hydrophobic and oleophobic properties, which can improve the water resistance, oil resistance, and solvent resistance of the sponge, and improve the stability of the sponge; the hydrophobic modified nano-alumina has good hydrophobic properties and system compatibility, and can construct a rough micro-nano structure on the surface of the sponge, synergizing with the viscosity-enhanced modified fluorosilicone resin to reduce surface energy and improve the water resistance, oil resistance, solvent resistance, and stability of the sponge.

[0007] Preferably, the raw materials for preparing the tackifying modified fluorosilicone resin include tannic acid grafted silane and fluorine-containing silane.

[0008] The tackified modified fluorosilicone resin obtained by the reaction of tannic acid grafted silane and fluorine-containing silane has good adhesion properties and can form a uniform and dense cross-linked network structure on the surface of the sponge, thereby enhancing the mechanical properties of the sponge and improving its compressive strength and tensile strength.

[0009] Preferably, the raw materials for preparing the tannic acid grafted silane include tannic acid and 11-bromondecyltriethoxysilane.

[0010] Tannic acid has good adhesion properties and reactivity. The abundant phenolic hydroxyl groups can undergo etherification reaction with 11-bromodencyltriethoxysilane to improve the adhesion properties of silane. Tannic acid has good antioxidant properties and can scavenge free radicals to improve the stability of the sponge in high temperature environments. Tannic acid can also adjust the surface microstructure of the viscosity-enhancing modified fluorosilicone resin, optimize the distribution of fluorine elements, reduce surface energy, and improve hydrophobicity and oleophobicity.

[0011] Preferably, the fluorine-containing silane includes perfluorohexylethyltrichlorosilane and heptadecafluorodecyltrimethoxysilane.

[0012] Perfluorohexylethyltrichlorosilane and heptadecafluorodecyltrimethoxysilane have good hydrophobic and oleophobic properties. Fluorine atoms have low surface energy. The long-chain fluorocarbon groups in the fluorinated silanes can be tightly arranged on the surface of the sponge, while reducing the wetting effect of solvents and improving the water resistance, oil resistance and solvent resistance of the sponge. Fluorinated silanes have good high temperature resistance and chemical corrosion resistance, which can improve the stability of the sponge and reduce the damage to the sponge performance caused by harsh environments.

[0013] Preferably, the mass ratio of the tannic acid grafted silane, perfluorohexylethyltrichlorosilane and heptadecafluorodecyltrimethoxysilane is (0.6-0.8):1:1.5.

[0014] The thickening-modified fluorosilicone resin prepared according to the above mass ratio has good water resistance, oil resistance and solvent resistance, and can improve the stability and mechanical properties of the sponge.

[0015] Preferably, the raw materials for preparing the hydrophobically modified nano-alumina include nano-alumina, maleic rosin acid and acyl chloride.

[0016] Preferably, the raw materials for preparing the maleic rosin acid include maleic anhydride and rosin acid.

[0017] Nano-alumina can help the modifier build a rough micro-nano structure on the surface of the sponge, further improving the hydrophobic and oleophobic properties of the modified sponge; maleopimaric acid obtained by the reaction of maleic anhydride and rosin acid has good reaction performance, and its reaction activity is further improved after reaction with acyl chloride, and can serve as a connecting bridge between nano-alumina and sponge, so that the hydrophobically modified nano-alumina can react with the sponge to obtain a uniform and dense modified layer; nano-alumina has high strength and hardness, and can improve the compression and tensile properties of the sponge, and improve the density and stability of the sponge.

[0018] Preferably, the mass ratio of the nano-alumina, maleic rosin acid and acyl chloride is (1.5-2):1:0.32.

[0019] The hydrophobically modified nano-alumina prepared according to the above mass ratio has good hydrophobic and oleophobic properties and reaction performance, and can improve the tensile strength, compression resistance and stability of the modified sponge.

[0020] Preferably, the leveling agent comprises acrylamide.

[0021] In a second aspect, the present application provides a method for preparing a sponge material modifier, using the following technical solution: A preparation method for a sponge material modifier comprises the following steps: The tackifier-modified fluorosilicone resin, the hydrophobic-modified nano-alumina and the leveling agent are dispersed in a solvent, and the sponge material modifier is obtained after stirring and homogenization.

[0022] The sponge material modifier prepared according to the above steps can improve the water resistance, oil resistance and solvent resistance of the sponge. The rough three-dimensional fluorosilicone resin network constructed on the sponge surface can improve the tensile and compression resistance of the sponge while improving stability.

[0023] In summary, the present application includes at least one of the following beneficial technical effects: 1. The viscosity-enhanced modified fluorosilicone resin improves the reactivity and adhesion of the modifier by introducing sticky groups, so that the modifier can react with the sponge and thus firmly bond. The fluorosilicone resin has good stability, low surface energy, and hydrophobic and oleophobic properties, which can improve the water resistance, oil resistance, and solvent resistance of the sponge, and improve the stability of the sponge; the hydrophobically modified nano-alumina has good hydrophobic properties and system compatibility, and can construct a rough micro-nano structure on the surface of the sponge, synergizing with the viscosity-enhanced modified fluorosilicone resin to reduce surface energy and improve the water resistance, oil resistance, solvent resistance, and stability of the sponge.

[0024] 2. Tannic acid has good adhesion and reactivity. The rich phenolic hydroxyl groups can react with 11-bromondecyltriethoxysilane to undergo etherification reaction, thus improving the adhesion of silane. Tannic acid has good antioxidant properties, can remove free radicals, and improve the resistance and stability of the sponge to high temperature environments. Tannic acid can also adjust the surface microstructure of the viscosity-modified fluorosilicone resin, optimize the distribution of fluorine elements, reduce surface energy, and improve hydrophobicity and oleophobicity. Perfluorohexylethyltrichlorosilane and heptadecafluorodecyltrimethoxysilane have good hydrophobic and oleophobic properties. Fluorine atoms have low surface energy. The long-chain fluorocarbon groups in fluorinated silanes can be closely arranged on the surface of the sponge, while reducing the wetting effect of solvents, thus improving the water resistance, oil resistance, and solvent resistance of the sponge. Fluorinated silanes have good high temperature resistance and chemical corrosion resistance, which can improve the stability of the sponge and reduce the damage to the sponge performance caused by harsh environments.

[0025] 3. Nano-alumina can help the modifier to construct a rough micro-nano structure on the surface of the sponge, further improving the hydrophobic and oleophobic properties of the modified sponge; maleic pimaric acid obtained by the reaction of maleic anhydride and rosin acid has good reaction performance, and its reaction activity is further improved after reaction with acyl chloride, which can serve as a connecting bridge between nano-alumina and sponge, so that the hydrophobically modified nano-alumina can react with the sponge to obtain a uniform and dense modified layer; nano-alumina has high strength and hardness, which can improve the compression and tensile properties of the sponge, and improve the density and stability of the sponge. DETAILED DESCRIPTION

[0026] The present application discloses a sponge material modifier and a preparation method thereof. The raw materials used in the present application can be obtained from commercially available raw materials unless otherwise specified. The present application is further described in detail below in conjunction with the examples: Raw materials: Tannic acid (CAS: 1401-55-4), 11-bromodencyltriethoxysilane (CAS No.: 200138-14-3), DMF (CAS No.: 68-12-2), perfluorohexylethyltrichlorosilane (CAS No.: 78560-45-9), heptadecafluorodecyltrimethoxysilane (CAS No.: 83048-65-1), rosin acid (CAS No.: 514-10-3), maleic anhydride (CAS No.: 108-31-6 ), dibutyltin dilaurate (CAS No.: 77-58-7), acyl chloride is oxalyl chloride (CAS No.: 79-37-8), nano alumina is purchased from Huifu Nano, p-dimethylaminopyridine (CAS No.: 1122-58-3), leveling agent is acrylamide (CAS No.: 79-06-1), solvent is butyl acetate (CAS No.: 123-86-4), catechol (CAS No.: 120-80-9), fluorosilicone resin is purchased from Shenzhen Jialede Chemical Technology Co., Ltd.

[0027] Example 1 Preparation of tackified modified fluorosilicone resin Under a nitrogen atmosphere, 18.45 kg of tannic acid and 27 kg of potassium carbonate were mixed and dispersed in 100 L of DMF to obtain a mixed solution, 21.55 kg of 11-bromodencyltriethoxysilane was dispersed in 50 L of DMF to obtain a silane dispersion, and the silane dispersion was added to the mixed solution under the protection of a nitrogen atmosphere. The temperature was raised to 85° C. and the reaction was stirred at a speed of 800 rpm for 12 hours. After cooling to below 30° C., the solid residue was removed by suction filtration, the filtrate was precipitated with isopropyl ether, the precipitate was dissolved with ethanol, and then precipitated again with isopropyl ether, and the secondary precipitate was dried in an oven at 40° C. to obtain tannic acid grafted silane.

[0028] 19.35 kg of tannic acid grafted silane, 32.26 kg of perfluorohexylethyltrichlorosilane and 48.39 kg of heptadecafluorodecyltrimethoxysilane were mixed and dispersed in anhydrous ethanol. 40 L of deionized water was added to the silane dispersion under stirring at 200 rpm and in a 50°C water bath. The addition was completed within 30 minutes. The reaction was continued by heat preservation and stirring for 30 minutes to obtain a product solution. The product solution was rotary evaporated to remove the solvent to obtain a tackified modified fluorosilicone resin.

[0029] Preparation of hydrophobically modified nano-alumina 15.1 kg of rosin acid, 4.9 kg of maleic anhydride and 0.3 kg of dibutyltin dilaurate were mixed and dispersed, ammonia was introduced for 15 minutes, and then the material was heated to melt, then stirred at a speed of 200 rpm and heated to 180°C. After reacting at 180°C for 4 hours, the product was cooled to 110°C and poured into turpentine oil, crystallized at room temperature, and the crystals were filtered and washed with ethanol for 3 times. The washed crystals were dried in a vacuum oven at 60°C to obtain maleopimaric acid.

[0030] 10.64 kg of maleopimaric acid was dissolved in 20 L of tetrahydrofuran to obtain a maleopimaric acid solution, 3.4 kg of acid chloride was added to the maleopimaric acid solution within 2 h, and the mixture was stirred at 200 rpm for 6 h, and then rotary evaporated to obtain maleopimaric acid chloride.

[0031] 15.96 kg of nano-alumina was dispersed in 50 L of toluene solution, and an alumina dispersion was obtained after ultrasonic treatment. The maleimuramoyl chloride and 2 kg of p-dimethylaminopyridine prepared above were added to the alumina dispersion, and the mixture was reacted at 60° C. for 8 h. A precipitate was obtained after centrifugation. The precipitate was washed twice by centrifugation with isopropanol and anhydrous ethanol, and the washed precipitate was dried in a vacuum oven at 80° C. to obtain hydrophobically modified nano-alumina.

[0032] Preparation of sponge material modifier 60 kg of tackifying modified fluorosilicone resin, 10 kg of hydrophobic modified nano-alumina and 3 kg of leveling agent were dispersed in 80 kg of solvent, stirred at a speed of 200 rpm for 1 hour, and homogenized to obtain a sponge material modifier.

[0033] Example 2 Preparation of tackified modified fluorosilicone resin Under a nitrogen atmosphere, 18.45 kg of tannic acid and 27 kg of potassium carbonate were mixed and dispersed in 100 L of DMF to obtain a mixed solution, 21.55 kg of 11-bromodencyltriethoxysilane was dispersed in 50 L of DMF to obtain a silane dispersion, and the silane dispersion was added to the mixed solution under the protection of a nitrogen atmosphere. The temperature was raised to 85° C. and the reaction was stirred at a speed of 800 rpm for 12 hours. After cooling to below 30° C., the solid residue was removed by suction filtration, the filtrate was precipitated with isopropyl ether, the precipitate was dissolved with ethanol, and then precipitated again with isopropyl ether, and the secondary precipitate was dried in an oven at 40° C. to obtain tannic acid grafted silane.

[0034] 24.24 kg of tannic acid grafted silane, 30.3 kg of perfluorohexylethyltrichlorosilane and 45.46 kg of heptadecafluorodecyltrimethoxysilane were mixed and dispersed in anhydrous ethanol. 40 L of deionized water was added to the silane dispersion under stirring at 200 rpm and in a 50°C water bath. The addition was completed within 30 minutes. The reaction was continued by heat preservation and stirring for 30 minutes to obtain a product solution. The product solution was rotary evaporated to remove the solvent to obtain a tackified modified fluorosilicone resin.

[0035] Preparation of hydrophobically modified nano-alumina 15.1 kg of rosin acid, 4.9 kg of maleic anhydride and 0.3 kg of dibutyltin dilaurate were mixed and dispersed, ammonia was introduced for 15 minutes, and then the material was heated to melt, then stirred at a speed of 200 rpm and heated to 180°C. After reacting at 180°C for 4 hours, the product was cooled to 110°C and poured into turpentine oil, crystallized at room temperature, and the crystals were filtered and washed with ethanol for 3 times. The washed crystals were dried in a vacuum oven at 60°C to obtain maleopimaric acid.

[0036] 9.04 kg of maleopimaric acid was dissolved in 20 L of tetrahydrofuran to obtain a maleopimaric acid solution, 2.89 kg of acid chloride was added to the maleopimaric acid solution within 2 h, and the mixture was stirred at 200 rpm for 6 h, followed by rotary evaporation to obtain maleopimaric acid chloride.

[0037] 18.07 kg of nano-alumina was dispersed in 50 L of toluene solution, and an alumina dispersion was obtained after ultrasonic treatment. The maleopimaroyl chloride and 2 kg of p-dimethylaminopyridine prepared above were added to the alumina dispersion, and the mixture was reacted at 60° C. for 8 h. A precipitate was obtained after centrifugation. The precipitate was washed twice by centrifugation with isopropanol and anhydrous ethanol, and the washed precipitate was dried in a vacuum oven at 80° C. to obtain hydrophobically modified nano-alumina.

[0038] Preparation of sponge material modifier 80 kg of tackifying modified fluorosilicone resin, 20 kg of hydrophobic modified nano-alumina and 5 kg of leveling agent were dispersed in 100 kg of solvent, stirred at a speed of 200 rpm for 1 hour, and homogenized to obtain a sponge material modifier.

[0039] Example 3 Preparation of tackified modified fluorosilicone resin Under a nitrogen atmosphere, 18.45 kg of tannic acid and 27 kg of potassium carbonate were mixed and dispersed in 100 L of DMF to obtain a mixed solution, 21.55 kg of 11-bromodencyltriethoxysilane was dispersed in 50 L of DMF to obtain a silane dispersion, and the silane dispersion was added to the mixed solution under the protection of a nitrogen atmosphere. The temperature was raised to 85° C. and the reaction was stirred at a speed of 800 rpm for 12 hours. After cooling to below 30° C., the solid residue was removed by suction filtration, the filtrate was precipitated with isopropyl ether, the precipitate was dissolved with ethanol, and then precipitated again with isopropyl ether, and the secondary precipitate was dried in an oven at 40° C. to obtain tannic acid grafted silane.

[0040] 21.875 kg of tannic acid grafted silane, 31.25 kg of perfluorohexylethyltrichlorosilane and 46.875 kg of heptadecafluorodecyltrimethoxysilane were mixed and dispersed in anhydrous ethanol. 40 L of deionized water was added to the silane dispersion under stirring at 200 rpm and in a 50°C water bath. The addition was completed within 30 minutes. The reaction was continued by heat preservation and stirring for 30 minutes to obtain a product solution. The product solution was rotary evaporated to remove the solvent to obtain a tackified modified fluorosilicone resin.

[0041] Preparation of hydrophobically modified nano-alumina 15.1 kg of rosin acid, 4.9 kg of maleic anhydride and 0.3 kg of dibutyltin dilaurate were mixed and dispersed, ammonia was introduced for 15 minutes, and then the material was heated to melt, then stirred at a speed of 200 rpm and heated to 180°C. After reacting at 180°C for 4 hours, the product was cooled to 110°C and poured into turpentine oil, crystallized at room temperature, and the crystals were filtered and washed with ethanol for 3 times. The washed crystals were dried in a vacuum oven at 60°C to obtain maleopimaric acid.

[0042] 9.77 kg of maleopimaric acid was dissolved in 20 L of tetrahydrofuran to obtain a maleopimaric acid solution, 3.13 kg of acid chloride was added to the maleopimaric acid solution within 2 h, and the mixture was stirred at 200 rpm for 6 h, followed by rotary evaporation to obtain maleopimaric acid chloride.

[0043] 17.1 kg of nano-alumina was dispersed in 50 L of toluene solution, and an alumina dispersion was obtained after ultrasonic treatment. The maleimuramoyl chloride and 2 kg of p-dimethylaminopyridine prepared above were added to the alumina dispersion, and the mixture was reacted at 60° C. for 8 h. A precipitate was obtained after centrifugation. The precipitate was washed twice by centrifugation with isopropanol and anhydrous ethanol, and the washed precipitate was dried in a vacuum oven at 80° C. to obtain hydrophobically modified nano-alumina.

[0044] Preparation of sponge material modifier 70 kg of tackifying modified fluorosilicone resin, 15 kg of hydrophobic modified nano-alumina and 4 kg of leveling agent were dispersed in 90 kg of solvent, stirred at a speed of 200 rpm for 1 hour, and homogenized to obtain a sponge material modifier.

[0045] Example 4 Example 4 is based on Example 3. The only difference between Example 4 and Example 3 is that in Example 4, the amount of tannic acid grafted silane used is 16.67 kg, the amount of perfluorohexylethyltrichlorosilane used is 33.33 kg, and the amount of heptadecafluorodecyltrimethoxysilane used is 50 kg.

[0046] Example 5 Example 5 is based on Example 3. The only difference between Example 5 and Example 3 is that in Example 5, the amount of tannic acid grafted silane used is 26.47 kg, the amount of perfluorohexylethyltrichlorosilane used is 29.41 kg, and the amount of heptadecafluorodecyltrimethoxysilane used is 44.12 kg.

[0047] Example 6 Example 6 is based on Example 3. The only difference between Example 6 and Example 3 is that in Example 6, tannic acid is replaced by catechol when preparing tannic acid-grafted silane.

[0048] Example 7 Example 7 is based on Example 3. The only difference between Example 7 and Example 3 is that in Example 7, heptadecafluorodecyltrimethoxysilane is not added when preparing the tackifying modified fluorosilicone resin.

[0049] Example 8 Example 8 is based on Example 3. The only difference between Example 8 and Example 3 is that in Example 8, the amount of nano-alumina used is 12.93 kg, the amount of maleopimaric acid used is 12.93 kg, and the amount of acyl chloride used is 4.14 kg.

[0050] Example 9 Example 9 is based on Example 3. The only difference between Example 9 and Example 3 is that in Example 9, the amount of nano-alumina used is 19.63 kg, the amount of maleopimaric acid used is 7.85 kg, and the amount of acyl chloride used is 2.52 kg.

[0051] Example 10 Example 10 is based on Example 3. The only difference between Example 10 and Example 3 is that maleopimaric acid is replaced by abietic acid when preparing hydrophobically modified nano-alumina in Example 10.

[0052] Embodiment 11 Example 11 is based on Example 3. The only difference between Example 11 and Example 3 is that no acyl chloride is added when preparing the hydrophobically modified nano-alumina in Example 11.

[0053] Comparative Example 1 Comparative Example 1 is based on Example 3, and the only difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, the tackifying modified fluorosilicone resin is replaced by fluorosilicone resin.

[0054] Comparative Example 2 Comparative Example 2 is based on Example 3, and the only difference between Comparative Example 2 and Example 3 is that in Comparative Example 2, the hydrophobically modified nano-alumina is replaced by nano-alumina.

[0055] Performance testing The sponge was immersed in the prepared sponge material modifier at 60° C. for 15 min, the sponge material modifier absorbed by the sponge was squeezed out, and the sponge was dried and cured at 100° C. for 6 h to obtain a sample for testing.

[0056] (1) Contact angle test: The contact angle of the test sample with respect to water and salad oil was tested three times for each sample. The average value was taken after measurement and the results are recorded in Table 1.

[0057] (2) Select "ISO 1798-2008" as the standard to test the tensile strength of the sample; place the sample in a damp heat aging box at 80°C and 95% humidity for 120 hours, and test the tensile strength of the sample after curing. Prepare three samples for each sample, take the average value after measurement, and record the results in Table 1.

[0058] (3) ISO 1856-2007 was selected as the standard to test the compression permanent deformation rate of the sample. Three samples were prepared for each sample, and the average value was taken after measurement. The results are recorded in Table 1.

[0059] Table 1 Test results of water-oil contact angle, tensile strength, compression strength and stability of modified sponge It can be seen from Table 1 that the water contact angle of Examples 1-3 is greater than 162°, the oil contact angle is greater than 139°, the tensile strength is greater than 358KPa, the tensile strength after aging is greater than 297KPa, and the compression permanent deformation rate is less than 4.2%. It can be seen that the sponge material modifier prepared in the present application can improve the water resistance, oil resistance, tensile resistance, compression resistance and stability of the sponge.

[0060] As can be seen from Table 1, the only difference between Examples 4 and 5 and Example 3 is that the mass ratio of tannic acid grafted silane, perfluorohexylethyltrichlorosilane and heptadecafluorodecyltrimethoxysilane in Example 4 is 0.5:1:1.5, and the mass ratio of tannic acid grafted silane, perfluorohexylethyltrichlorosilane and heptadecafluorodecyltrimethoxysilane in Example 5 is 0.9:1:1.5. Compared with Example 3, the water resistance, oil resistance, tensile strength, compression resistance and stability of Examples 4 and 5 are all reduced. This is because the mass ratio of tannic acid grafted silane, perfluorohexylethyltrichlorosilane and heptadecafluorodecyltrimethoxysilane is not within the specified range. Too little tannic acid will reduce the adhesion between the modifier and the sponge and affect the bonding strength; too much tannic acid will reduce the stability of the fluorocarbon resin, thereby reducing the water resistance, oil resistance, tensile strength, compression resistance and stability.

[0061] As can be seen from Table 1, the only difference between Examples 6 and 7 and Example 3 is that: in Example 6, tannic acid is replaced by catechol when preparing tannic acid-grafted silane, and in Example 7, heptadecafluorodecyltrimethoxysilane is not added when preparing the tackified modified fluorosilicone resin. Compared with Example 3, Examples 6 and 7 have reduced water resistance, oil resistance, tensile strength, compression resistance and stability; this is because if tannic acid is replaced by catechol, the number of active functional groups of catechol is less, and the adhesion performance is reduced, thereby affecting the modification effect of the modifier; without adding heptadecafluorodecyltrimethoxysilane, there is a lack of the compounding effect of multiple silanes, and the performance of the tackified modified fluorosilicone resin is reduced, thereby reducing the water resistance, oil resistance, tensile strength, compression resistance and stability.

[0062] As can be seen from Table 1, the only difference between Examples 8 and 9 and Example 3 is that the mass ratio of nano-alumina, maleic rosin acid and acyl chloride in Example 8 is 1:1:0.32, and the mass ratio of nano-alumina, maleic rosin acid and acyl chloride in Example 9 is 2.5:1:0.32. Compared with Example 3, Examples 8 and 9 have reduced water resistance, oil resistance, tensile strength, compression resistance and stability; this is because the mass ratio of nano-alumina, maleic rosin acid and acyl chloride is not within the specified range, and the degree of modification will affect the dispersibility, system compatibility and reaction performance of nano-alumina, and further affect the structural morphology and stability constructed by the modifier on the sponge surface, thereby reducing water resistance, oil resistance, tensile strength, compression resistance and stability.

[0063] As can be seen from Table 1, the only difference between Examples 10 and 11 and Example 3 is that: in Example 10, maleopimaric acid is replaced by rosin acid when preparing the hydrophobically modified nano alumina, and in Example 11, no acyl chloride is added when preparing the hydrophobically modified nano alumina. Compared with Example 3, Examples 10 and 11 have reduced water resistance, oil resistance, tensile strength, compression resistance and stability; this is because the components used to modify the nano alumina are replaced, maleopimaric acid is replaced by rosin acid, and there is a lack of modification treatment with maleic anhydride, so the reaction performance is reduced. No acyl chloride is added, and the reactivity of the carboxylic acid group is lower than that of the acyl chloride group, which will affect the reaction performance of the hydrophobically modified nano alumina, thereby reducing the water resistance, oil resistance, tensile strength, compression resistance and stability.

[0064] As can be seen from Table 1, the only difference between Comparative Example 1 and Example 3 is that Comparative Example 1 replaces the tackified modified fluorosilicone resin with fluorosilicone resin. Compared with Example 3, the water resistance, oil resistance, tensile strength, compression resistance and stability of Comparative Example 1 are significantly reduced; this is because the tackified modified fluorosilicone resin is replaced with fluorosilicone resin, and there is a lack of tackified modification treatment, the reaction performance and adhesion performance of the fluorosilicone resin are reduced, and the modification effect of the modifier is reduced, so that the water resistance, oil resistance, tensile strength, compression resistance and stability are significantly reduced.

[0065] As can be seen from Table 1, the only difference between Comparative Example 2 and Example 3 is that: Comparative Example 2 replaces the hydrophobic modified nano-alumina with nano-alumina. Compared with Example 3, Comparative Example 2 has significantly decreased water resistance, oil resistance, tensile strength, compression resistance and stability. This is because the hydrophobic modified nano-alumina is replaced with nano-alumina, and there is a lack of modification treatment, so the dispersibility and compatibility of nano-alumina are reduced, and the reaction performance is reduced, thereby affecting the toughening and rough surface construction in the system. The role, which leads to a significant decrease in the water resistance, oil resistance, tensile strength, compression resistance and stability of the sponge.

[0066] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of ​​the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A sponge material modifier, characterized in that: The composition includes the following components in parts by weight: 60-80 parts of tackified modified fluorosilicone resin 10-20 parts of hydrophobically modified nano-alumina 3-5 parts of leveling agent 80-100 parts of solvent.

2. A sponge material modifier according to claim 1, characterized in that: The raw materials for preparing the tackifying modified fluorosilicone resin include tannic acid grafted silane and fluorine-containing silane.

3. A sponge material modifier according to claim 2, characterized in that: The raw materials for preparing the tannic acid grafted silane include tannic acid and 11-bromondecyltriethoxysilane.

4. A sponge material modifier according to claim 3, characterized in that: The fluorine-containing silane includes perfluorohexylethyltrichlorosilane and heptadecafluorodecyltrimethoxysilane.

5. A sponge material modifier according to claim 4, characterized in that: The mass ratio of the tannic acid grafted silane, perfluorohexylethyltrichlorosilane and heptadecafluorodecyltrimethoxysilane is (0.6-0.8):1:1.

5.

6. A sponge material modifier according to claim 1, characterized in that: The raw materials for preparing the hydrophobically modified nano-alumina include nano-alumina, maleic rosin acid and acyl chloride.

7. A sponge material modifier according to claim 6, characterized in that: The raw materials for preparing the maleic rosin acid include maleic anhydride and rosin acid.

8. A sponge material modifier according to claim 7, characterized in that: The mass ratio of the nano-alumina, maleic rosin acid and acyl chloride is (1.5-2):1:0.

32.

9. A sponge material modifier according to claim 1, characterized in that: The leveling agent includes acrylamide.

10. A method for preparing the sponge material modifier according to claim 1, characterized in that: The steps include: The tackifier-modified fluorosilicone resin, the hydrophobic-modified nano-alumina and the leveling agent are dispersed in a solvent, and the sponge material modifier is obtained after stirring and homogenization.